Therapy of chronic hepatitis C in people who inject drugs: focus on adherence - Sona Frankova; Zuzana Jandova; Gabriela Jinochova; Miluse Kreidlova; Dusan Merta; Jan Sperl (BMC, 2021)
Abstract Background Intravenous drug use (IVDU) represents the major factor of HCV transmission, but the treatment uptake among people who inject drugs (PWID) remains low owing to a false presumption of low efficacy. The aim of our study was to assess treatment efficacy in PWID and factors determining adherence to therapy. Methods A total of 278 consecutive patients starting DAA (direct-acting antivirals) therapy were included, divided into two groups: individuals with a history of IVDU, PWID group (N = 101) and the control group (N = 177) without a history of IVDU. Results Sustained virological response 12 weeks after the end of therapy (SVR12) was achieved by 99/101 (98%) and 172/177 (98%) patients in the PWID and control group, respectively; in PWID group, two patients were lost to follow-up, and in the control group, four patients relapsed and one was lost to follow-up. PWID patients postponed appointments significantly more often, 29 (28.7%) in PWID versus 7 (4%) in the control group, p = 0.001. Thirteen of 101 (12.9%) and six of 177 (3.4%) patients in the PWID and in the control group, respectively, missed at least one visit (p < 0.01). However, postponing visits led to a lack of medication in only one PWID. In the PWID group, older age (p < 0.05; OR 1.07, 95% CI 1.00-1.20) and stable housing (p < 0.01; OR 9.70, 95% CI 2.10-56.20) were factors positively contributing to adherence. Contrarily, a stable job was a factor negatively influencing adherence (p < 0.05; OR 0.24, 95% CI 0.06-0.81). In the control group, none of the analyzed social and demographic factors had an impact on adherence to therapy. Conclusions In PWID, treatment efficacy was excellent and was comparable with SVR of the control group. Stable housing and older age contributed to a better adherence to therapy.